Pathway-Based High-Throughput Chemical Screen Identifies Compounds That Decouple Heterochromatin Transformations. (September 2019) - MacDonald, Ian A.; Butler, Kyle V.; Herring, Laura E.; Clinkscales, Sarah E.; Yelagandula, Ramesh; Stecher, Karin; Bell, Oliver; Graves, Lee M.; Jin, Jian; Hathaway, Nathaniel A.
Heterochromatin protein 1 (HP1) facilitates the formation of repressive heterochromatin domains by recruiting histone lysine methyltransferase enzymes to chromatin, resulting in increased levels of histone H3K9me3. To identify chemical inhibitors of the HP1-heterochromatin gene repression pathway, we combined a cell-based assay that utilized chemical-mediated recruitment of HP1 to an endogenous active gene with high-throughput flow cytometry. Here we characterized small molecule inhibitors that block HP1-mediated heterochromatin formation. Our lead compounds demonstrated dose-dependent inhibition of HP1-stimulated gene repression and were validated in an orthogonal cell-based system. One lead inhibitor was improved by a change in stereochemistry, resulting in compound 2, which was further used to decouple the inverse relationship between H3K9 and H3K4 methylation states. We identified molecular components that bound compound 2, either directly or indirectly, by chemical affinity purification with a biotin-tagged derivative, followed by quantitative proteomic techniques. In summary, our pathway-based chemical screening approach resulted in the discovery of new inhibitors of HP1-mediated heterochromatin formation while identifying exciting new molecular interactions in the pathway to explore in the future. This modular platform can be expanded to test a wide range of chromatin modification pathways yielding inhibitors that are cell permeable and function in a physiologically relevant setting.